Asian independence leaders - Wakin, Eric (Global profiles, 1997)
Profiles nine men, including Sun Yat-sen of China, Gandhi of India, Ho Chi Minh of Vietnam, and Emilio Aguinaldo of the Philippines, who struggled to free their respective countries from colonial rule or monarchy.